2023
DOI: 10.3390/children10071230
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and Pharmacological Interventions and Treatment Indications for the Management of Obesity in Children and Adolescents

Abstract: Obesity is a multifactorial chronic impairment that further decreases quality of life and life expectancy. Worldwide, childhood obesity has become a pandemic health issue causing several comorbidities that frequently present already in childhood, including cardiovascular (hypertension, dyslipidemia), metabolic (Type 2 diabetes mellitus, fatty liver disease, metabolic syndrome), respiratory, gastrointestinal and musculoskeletal disorders. In addition, obese children frequently experience stress and psychosocial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…Several intervention studies on obese and overweight pediatrics (aged 6–16 years) have demonstrated that weight loss was successful in decreasing BP in pediatrics [ 25 ]. These intervention studies (5- to 12-month) have incorporated education, physical activity, and diet and demonstrated that intervention was effective in decreasing SBP [ 27 , 28 ]. In a recent large retrospective study that recruited 101,606 of pediatrics (aged 3–17 years) who were followed for several years, authors found that obese and severely obese participants had increased BP at baseline and greater odds of developing hypertension in adulthood compared with pediatrics with normal BMI [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several intervention studies on obese and overweight pediatrics (aged 6–16 years) have demonstrated that weight loss was successful in decreasing BP in pediatrics [ 25 ]. These intervention studies (5- to 12-month) have incorporated education, physical activity, and diet and demonstrated that intervention was effective in decreasing SBP [ 27 , 28 ]. In a recent large retrospective study that recruited 101,606 of pediatrics (aged 3–17 years) who were followed for several years, authors found that obese and severely obese participants had increased BP at baseline and greater odds of developing hypertension in adulthood compared with pediatrics with normal BMI [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the plethora of successful interventions to prevent and manage childhood obesity [ 27 , 28 ], most lifestyle modification programs done in Saudi Arabia focused on adult obesity and individuals at high risk for diabetes [ 29 , 30 ], while pediatric obesity studies are mostly observational [ 31 , 32 ]. The current study investigates the efficacy of attendance-based adherence to a lifestyle obesity management program and its association with changes in obesity indices and hypertension in a cohort of Arab children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, lifestyle interventions are usually combined with pharmacological or dietary interventions to enhance the efficacy of these treatments [1]. This integrative approach is especially crucial when obesity reaches severe levels, as lifestyle changes alone often become insufficient [128][129][130]. Thus, most clinical treatment approaches for childhood obesity include combined treatment with lifestyle interventions as an effective integrative approach.…”
Section: Other Approachesmentioning
confidence: 99%
“…However, the reluctance of parents to be involved in PO prevention activities, a lack of adequate knowledge, and financial concerns are the most commonly described obstacles in this field [110]. Recently, the major options for PO management, such as lifestyle modification approaches and pharmacological therapies, as well as the treatment indications for the general practitioner, have been reviewed [111]. Medications, including orlistat, phentermine, phentermine/topiramate, and GLP1 receptor agonists (liraglutide and semaglutide), have also been approved for patients who are 12 years old and older.…”
Section: Management Of Pediatric Obesity and Strategies For Pediatric...mentioning
confidence: 99%